A study of metaphors in advertising in Indian and UK editions of ELLE and VOGUE - Agarwal, Nidhi (2008)
This thesis is a study of the ways advertisers use conceptual metaphors in order to creatively communicate with their customers. The purpose of this study is to analyze the metaphorical content of various advertisements and evaluate the creativity behind these advertisements. A conceptual framework was established through the evaluation of literature and a few issues were identified, which became the basis of further study.